GIS tools in geology based on GMT software package - Zui, Vladimir I. (Journal of the Belarusian State University. Geography and Geology, 2025)
The article provides brief information about the Generic Mapping Tools (GMT) software package, which is included in the training programme for undergraduate and graduate students of geological specialties at the faculty of geography and geoinformatics of the Belarusian State University as one of the GIS tools. It allows creating high-quality graphic figures and animations when completing term papers and theses, writing master’s dissertations, scientific articles, etc. The main functional capabilities of the package are considered, and its main differences from commercial GIS are noted. Examples of using the GMT software package to solve geological and geophysical problems in the process of mastering this GIS tool by students are considered.